1983
DOI: 10.1159/000238166
|View full text |Cite
|
Sign up to set email alerts
|

Elimination Kinetics of Cefotaxime and Desacetyl Cefotaxime in Patients with Renal Insufficiency and during Hemodialysis

Abstract: The pharmacokinetics of cefotaxime, a new semi-synthetic cephalosporin for injection, was studied in 30 subjects with various degrees of renal function after a single 1-gram intramuscular injection. Serum and urinary concentrations of cefotaxime and desacetyl cefotaxime were determined by high pressure liquid chromatography. The pharmacokinetic parameters of cefotaxime were obtained using a one-compartment open model. The mean serum half-life of the parent compound (cefotaxime), 0.87 h in normal subjects, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
10
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
6
10
0
Order By: Relevance
“…In our subjects, the urinary excretion of unchanged Ctx during the 6-h postinfusion period (approximately 61%) was in close agreement with values reported for adults with normal renal function (5,12,14). The CLR of Ctx in our subjects (0.174 liter/h per kg) was similar to that in adults with normal renal function (165 ml/min per 1.73 m2 or approximately 0.141 liter/h per kg) (29). The mean CL of Ctx in our subjects (0.289 liter/h per kg) was in close agreement with values reported for adults with normal renal function (approximately 0.234 to 0.307 liter/h per kg) after Ctx quantitation by HPLC (16,29).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our subjects, the urinary excretion of unchanged Ctx during the 6-h postinfusion period (approximately 61%) was in close agreement with values reported for adults with normal renal function (5,12,14). The CLR of Ctx in our subjects (0.174 liter/h per kg) was similar to that in adults with normal renal function (165 ml/min per 1.73 m2 or approximately 0.141 liter/h per kg) (29). The mean CL of Ctx in our subjects (0.289 liter/h per kg) was in close agreement with values reported for adults with normal renal function (approximately 0.234 to 0.307 liter/h per kg) after Ctx quantitation by HPLC (16,29).…”
Section: Discussionsupporting
confidence: 89%
“…The CLR of Ctx in our subjects (0.174 liter/h per kg) was similar to that in adults with normal renal function (165 ml/min per 1.73 m2 or approximately 0.141 liter/h per kg) (29). The mean CL of Ctx in our subjects (0.289 liter/h per kg) was in close agreement with values reported for adults with normal renal function (approximately 0.234 to 0.307 liter/h per kg) after Ctx quantitation by HPLC (16,29). The differences between CL of Ctx in our patients and that in full-term, newborn infants (2,26) were consistent with expected developmental differences in renal function and body mass-water relationships between the two age groups.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Cefotaxime is unique among the expanded-spectrum cephalosporins in that it is partially metabolized to desacetylcefotaxime, which retains 1/2 to 1/10th of the parent compound's antimicrobial activity (3,5). Both cefotaxime and desacetylcefotaxime pharmacokinetics were affected by renal dysfunction in adults (4,6,7). Approximately 40 to 60% of cefotaxime was excreted renally in adults with normal renal function (4,6,7).…”
mentioning
confidence: 99%
“…Both cefotaxime and desacetylcefotaxime pharmacokinetics were affected by renal dysfunction in adults (4,6,7). Approximately 40 to 60% of cefotaxime was excreted renally in adults with normal renal function (4,6,7). It has also been reported that the elimination half-life (t4/2) of the desacetyl metabolite was extended during renal dysfunction in adults (4,6,7).…”
mentioning
confidence: 99%